Qualidade total e cidadania: a experiência da Secretaria de Administração da Prefeitura de Salvador - Ramos, Adriana Lana (1996)
The present study is a reflection over the total quality management, trying to show the opportunities and limitations of this application to the brazilian public administration. The study assumes as object of analysis the Capability of Total Quality Program developed by the Municipal Cityhall of Salvador (BA) and implanted in the Secretariat of Administration since 1993. In this approach, the issue on quality is inserted in a more general analytical context, where the exerci se of citizenship is considered an outstanding compound to the effective and competent dynamics in public administration.